Water sources and urban expansion in Ruwa town in post-colonial Zimbabwe, 1986–2020 - Muzorewa, Terence T.; Nyandoro, Mark (White Horse Press, 2022)
Africa is experiencing phenomenal urban growth and myriad environmental challenges associated with urban sprawl. Zimbabwe, situated in the heart of the southern African region, is no exception to this rule. Urban population has continued to spike, with more than half the world's population residing in urban areas. Although Africa has less than forty per cent (33 per cent for Zimbabwe) of its population living in urban habitats, urban development has been on the rise as a result of the dynamic processes of industrialisation. In order to thrive, these human habitats required sustainable water sources. Private Land Developer Com-panies (PLDCs) in Ruwa Town, Zimbabwe, were placed at the core of water and other infrastructure expansion. Since the developers were thought to be endowed with financial resources, there were high expectations that the town was going to lead in public infrastructure development. However, this article shows that Ruwa failed to live up to the expected standards in the development of water facilities and other infrastructure to facilitate urban growth and development.